RELIGIOUS DISCOURSE IN NEWS REPORTS ON AL ZAYTUN ISLAMIC BOARDING SCHOOL - Yuliyanto, Andik; Khotimah, Khusnul; Pribadi, Farid (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2023)
This research discusses the construction of religious discourse in news reports on Al Zaytun Islamic Boarding School as an effort to understand contemporary issues. This paper employed the approach of critical discourse analysis based on Teun A. van Dijk’s theory. It aimed to explore how religious messages are prepared and delivered in news reports related to Al Zaytun Islamic boarding school. This research method involves analysis of news texts, focusing on structure, language pattern, and the choice of words that can influence readers’ understanding of issues contemporary. The findings of this research reveal that the construction of religious discourse in news reports on Al Zaytun Islamic Boarding School significantly influences how contemporary issues are presented and understood. The news journalists tend to use distinctive language It contains religious values and provides interpretation of certain latest events. Additionally, the structure of the discourse also creates a promotional narrative to understanding certain contemporary issues as well as reflects the complexity of the religious discourse construction in an effort to understand contemporary issues These findings can contribute to providing an understanding of the role of religious media in forming the public perception to various actual issues.